(untitled) (International Seven Journal of Multidisciplinary, 2023)
In soccer, physical preparation and muscle strengthening are of paramount importance to maximize the performance of athletes, but physical trainers, when systematizing and planning training, end up overestimating the anterior thigh muscles and underestimating the posterior thigh muscles, which are important. to improve the overall performance of the athlete. Thus, this study aimed to present strengthening and prevention methods to avoid muscle imbalance in soccer players. For the composition of this research, scientific articles published between the years 1994 to the most current 2023 were consulted. Injuries resulting from soccer are related to inadequate training, alterations that overload some body structures, causing muscle weakness, which may affect tendons and joints. Muscle strengthening and prevention International Seven Multidisciplinary Journal, São José dos Pinhais, v.2, n.2, p. 165-175, mar./apr., 2023 methods are important factors to maintain constant muscle balance during training and games, contributing to injury prevention and increasing the level of competitiveness in this sport. DOI:https://doi.org/10.56238/isevmjv2n2-002